Stress Erythropoiesis is a Key Inflammatory Response - Robert F. Paulson; Baiye Ruan; Siyang Hao; Yuanting Chen (Cells, 2020)
Bone marrow medullary erythropoiesis is primarily homeostatic. It produces new erythrocytes at a constant rate, which is balanced by the turnover of senescent erythrocytes by macrophages in the spleen. Despite the enormous capacity of the bone marrow to produce erythrocytes, there are times when it is unable to keep pace with erythroid demand. At these times stress erythropoiesis predominates. Stress erythropoiesis generates a large bolus of new erythrocytes to maintain homeostasis until steady state erythropoiesis can resume. In this review, we outline the mechanistic differences between stress erythropoiesis and steady state erythropoiesis and show that their responses to inflammation are complementary. We propose a new hypothesis that stress erythropoiesis is induced by inflammation and plays a key role in maintaining erythroid homeostasis during inflammatory responses.